Einige Betrachtungen über das Wachstum und Bestehen von ganzer transzendenter Lösungen partieller Differentialgleichungen - Streliz, S. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Ш. И. Стрелиц, Некоторые вопросы роста и существования целых трансцендентных решений уравнений в частных производных Š. Strelicas, Kai kurių lygčių dalinėmis išvestinėmis sveikų transcendentinių sprendinių augimo bei buvimo klausimai